Concussion in youth rugby union and rugby league: a systematic review - Kirkwood, G.; Parekh, N.; Ofori-Asenso, R.; Pollock, A. M. (British Journal of Sports Medicine, 2015)
Background: Children and adolescents who play rugby are at increased risk of concussion and its effects. Competitive rugby union and rugby league feature as major sports in the school sport curriculum in the UK. There is a need for a thorough understanding of the epidemiology of concussion in youth rugby, the mechanisms involved in injuries and predisposing risk factors. Data Sources: The publication databases Pubmed, Embase and SportDISCUS were searched in April 2014 for primary research studies of child and adolescent rugby union and rugby league (under 20 years) in English language with data on concussion injuries. The review was conducted within a larger all injury systematic review on rugby union and rugby league where key words used in the search included rugby, injury and concussion with child, adolescent, paediatric and youth. Results: There were 25 studies retrieved with data on child or adolescent rugby and concussion, 20 were on rugby union, three on rugby league and in two the code of rugby was unspecified. There was significant heterogeneity in the definitions of injuries and of concussion. The incidence of child and adolescent match concussion ranged from 0.2 to 6.9 concussions per 1000 player-hours for rugby union and was 4.6 and 14.7 concussions per 1000 player-hours for rugby league, equivalent to a probability of between 0.3% and 11.4% for rugby union and of 7.7% and 22.7% for rugby league. Conclusions: There is a significant risk of concussion in children and adolescents playing rugby union and rugby league evident from the studies included in this systematic review. There is a need for reliable data through routine monitoring and reporting in schools and clubs and in hospital emergency departments in order to inform prevention. Concussion protocols should be implemented and tested.